Environmental Impact Assessment of Sulaymaniyah Solid Waste Dumpsite Using Leachate and Soil Pollution Indices - Sura Mahdi Mohammad; Yaseen Ahmad Hamaamin; Nihad Bahaaldeen Salih (UHD Journal of Science and Technology)
Global urban population is rising that resulting more waste production. Globally, municipal solid waste (MSW) generation considered as a serious threat on the global environment and human wellbeing. Leachate from solid waste dumps poses significant environmental and health risks, particularly due to contamination in soil and water caused by heavy metals. In this study, environmental impacts of MSW are assessed and estimated for Sulaymaniyah city, KRG, Iraq, which is located at 10 km south of the city in the Tanjaro dumpsite. Soil and leachate samples were collected and analyzed for various expected pollutant, to assess the environmental contamination through using pollution indices. For assessing the leachate pollution index (LPI), some parameters were determined, such as potential of hydrogen (pH), total dissolved solid, biochemical oxygen demand (BOD5), and chemical oxygen demand (COD), and chloride (Cl). LPI value (20.1377) is much higher than the related standards. High concentrations of metals, such as cadmium (Cd), iron (Fe), manganese (Mn), copper (Cu), chromium (Cr), nickel (Ni), and zinc (Zn), found in the soil near the site, however, the contamination level is not serious based on the checked pollution indices, such as pollution index (PI) and nemerow PI (PInemerow). PI for Cd, Fe, Mn, Cu, Cr, Ni, and Zn were 0.158, 0.024, 0.088, 0.176, 0.613, 0.786, and 0.225, respectively, whereas, PInemerow value was 0.606, which classified the soil as a non-contaminated soil. Results of this study reveals that the Tanjaro dumpsite needs an engineered landfill and decent leachate treatment right away; since present conditions far over safe limits and threaten soil and water quality.